CULTO IMPERIAL E O APOCALIPSE DE JOÃO Uma análise exegética de Ap 13,1-18 - Ribeiro, Gilvaldo Mendes (2008)
This dissertation investigates the narrative of the apocalyptic vision found in Ap 13,1-18. Its starting point is a question about the reality which influenced the author at the time of writing by using baffling language. The hypothesis is that John s Apocalypse which is an important source of the experiences of primitive Christianity at the end of the first century offers a strong criticism of the demands of adoration offered to the Roman authorities by means of the Imperial Cult. The images of the beasts described in Ap 13,1-18 express this theme by using provocative language grounded in the force of the word and mythical tradition of the Ancient Near East. In this way, the author demonizes and stigmatizes the expressions of official religion that treat the governors as divine beings as well as the promoters of the Imperial Cult in Asia Minor.(AU)